Interview granted by teacher Sônia Kramer - Márcia Buss Simão; Moema Helena K. de Albuquerque Kiehn (Universidade Federal de Santa Catarina, 2008)
In May of 2008 to Prof.. Sonia Kramer, a professor and researcher of Education (PUC - RIO and UERJ) was participating as evaluation, in a meeting of defense for public dissertation in UFSC and granted the Márcia Buss Simon Moema and Kiehn, researchers of the Centre for Studies and Research Education in Little Children - NUPEIN, the interview that follows .